PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 009 TELUK PAUH KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI - Asmina Asmina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low learning outcomes of students in the third grade of SD Negeri 009 TelukPauh Cerenti. The purpose of this study was to improve the learning outcomes of students in social sciences. Thedesign of this study uses school action research consisting of two cycles. From the analysis of research dataobtained that, teacher activity at the first meeting of the first cycle, the teacher activity score of 24 or 60%. Whileat the second meeting of the first cycle the number of teacher activity scores was 29 or 72.5%. At the firstmeeting of the cycle II the number of teacher activity scores was 35 or 87.5%. After second meeting cycles II, theteacher's activity score increases to 38 or 95. Student activities, cycle I gets a score of 23 or 57.5%. At thesecond meeting of the first cycle, the student activity score increased by 28 or 70%. Cycle II, the activity ofstudents gets an assessment score of 34 or 85%. While at the meeting of two cycles II, it became 37 or 92.5%.seen from the learning outcomes of Students, on the basic scores of students who completed only 7 students or58.33%. In the cycle I daily test, 8 students or 66.66% complete. In the second cycle students who complete asmany as 11 students or 91.66%. Based on the results of the study, it can be concluded that the application of theSnowball Throwing type of cooperative learning model can improve the learning outcomes of students in thethird grade of SD Negeri 009 Teluk Pauh Cerenti.